The Link Between Habitats and Carbon Accumulation From Natural Forest Regrowth in Borino Municipality (Southern Bulgaria) - Grigorov, Borislav (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Carbon accumulation in forests is an important step towards achieving better climate mitigation levels. The current research aims at uncovering the link between the NATURA 2000 habitats in Borino Municipality, Southern Bulgaria and the expected carbon sequestration from natural forest regrowth for the period 2020-2050.
Keywords: Natura 2000; carbon sequestration; forest; Bulgaria; sekwestracja dwutlenku węgla; las; Bułgaria